Method for preparing calcium sulfate hemihydrate by using calcium sulfate dihydrate

By reacting with additives such as tungstate or molybdate, sulfosuccinate, nano-alumina, etc., the crystal growth environment is adjusted, and the problems of low strength and small length diameter of hemihydrate calcium sulfate in the prior art are solved, and the improvement of high strength and length diameter is achieved.

CN119797785AActive Publication Date: 2025-04-11SHANDONG JIEDUN ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510311621.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-04-11
Estimated Expiration
2045-03-17

AI Technical Summary

Technical Problem

In the prior art, when using calcium sulfate dihydrate to prepare alpha-type calcium sulfate, the produced product is relatively weak, has a relatively small length and diameter, and is complex in the admixture composition, which is prone to ionization reactions and unnecessary precipitation interference.

Method used

By removing impurities, calcium sulfate dihydrate is mixed with additives such as tungstate or molybdate, sulfosuccinate, nano-alumina and water, it is placed in a high-pressure container to react, adjust the crystal growth environment, provide more nucleation points, and directionally control the growth path of the crystal, and inhibit the by-product crystal phase.

Benefits of technology

The preparation of high-strength and relatively large length and diameter is achieved, which improves the mechanical strength and morphological stability of the product and reduces the generation of impurities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of calcium sulfate hemihydrate, and provides a method for preparing calcium sulfate hemihydrate by using calcium sulfate dihydrate, and the method specifically comprises the following steps: S1, removing impurities from calcium sulfate dihydrate; s2, uniformly mixing the impurity-removed calcium sulfate dihydrate with an additive, then putting the mixture into a high-pressure container, and reacting for 20-30 minutes under the conditions of 0.1-2 MPa and 120-160 DEG C; the additive is prepared from the following components: tungstate or molybdate, sulfosuccinate, nano aluminum oxide and water; s3, after the reaction is finished, reactants are dried at the temperature of 100-120 DEG C, and calcium sulfate hemihydrate is obtained. The tungstate or molybdate and the sulfosuccinate in the additive are combined with the nano aluminum oxide, and the purpose of improving the length-diameter ratio and the mechanical strength of the alpha-type gypsum is achieved by adjusting the crystal growth environment, providing more nucleation points, directionally controlling the crystal growth path and inhibiting the byproduct crystal phase.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of calcium sulfate hemihydrate preparation, and in particular to a method for preparing calcium sulfate hemihydrate by utilizing calcium sulfate dihydrate. Background Art

[0002] The production process of citric acid is mainly based on fermentation. Lime milk (calcium hydroxide) is added to form calcium citrate precipitation, which is then acidified with sulfuric acid to produce citric acid. At the same time, gypsum is produced as a by-product. The main component of the by-product gypsum is calcium sulfate dihydrate (CaSO 4 ·2H 2 O), which would occupy land and cause environmental problems if directly piled up, uses citric acid by-product gypsum as raw material and produces hemihydrate calcium sulfate (CaSO 4 0.5H 2 O) and other building materials products can not only realize the comprehensive utilization of resources, but also reduce pollution to the environment.

[0003] Calcium sulfate hemihydrate has two crystal forms, α-type and β-type. Currently, there are three main methods for producing α-type calcium sulfate hemihydrate: autoclave, hydrothermal method and normal pressure salt solution method. The invention patent with publication number CN105948547A discloses a method for preparing α-type calcium sulfate hemihydrate using calcium sulfate dihydrate. The additive components used in this method are complex, and organic salts and inorganic salts will undergo ionization reactions, generating unnecessary precipitation or intermediate products, interfering with the normal formation of crystals, and the α-type calcium sulfate hemihydrate finally generated has low strength and a smaller aspect ratio. Therefore, a method for preparing calcium sulfate hemihydrate with higher strength is needed. Summary of the invention

[0004] In view of this, the present invention proposes a method for preparing high-strength calcium sulfate hemihydrate with a large aspect ratio by using calcium sulfate dihydrate.

[0005] The technical solution of the present invention is achieved as follows: On the one hand, the present invention provides a method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate, comprising the following steps: S1, impurity removal of calcium sulfate dihydrate: Since the raw material calcium sulfate dihydrate comes from gypsum, a by-product of citric acid production, impurities need to be removed in order to obtain calcium sulfate hemihydrate with higher purity; S2, the calcium sulfate dihydrate after impurity removal is mixed evenly with an additive, and then placed in a high-pressure container, and reacted for 20 to 30 minutes at 0.1 to 2 MPa and 120 to 160° C.; the components of the additive include tungstate or molybdate, sulfosuccinate, nano-alumina and water; S3, after the reaction is completed, the reactant is dried at 100° C.-120° C. to obtain calcium sulfate hemihydrate.

[0006] Tungstate and molybdate regulate the crystallization dynamics, promote the directional growth of specific crystal faces, and improve the aspect ratio of gypsum whiskers. The principle is that the ions of tungstate and molybdate are adsorbed on the crystal interface or growth front, which can affect the energy distribution of the crystal, induce one-dimensional growth, and reduce the crystal extension behavior in other directions, thereby achieving the formation of slender whiskers.

[0007] Sulfosuccinates, as surfactants, can improve the uniformity of crystal growth and inhibit particle aggregation. Principle: Sulfosuccinate molecules have both hydrophilic and hydrophobic properties, and their sulfonic acid groups are easily adsorbed to the growth surface of gypsum crystals, such as certain side crystal planes, and the whiskers are extended from a single axis direction with the help of a stable growth plane.

[0008] Nano-alumina acts as a nucleating agent to increase the consistency of crystal morphology and improve the mechanical strength of the final product. Principle: Nano-alumina particles dispersed in the liquid phase provide more nucleation points, which can evenly distribute the geometric center of crystal formation, so that the generated crystals have a better aspect ratio and regular morphological characteristics.

[0009] Tungstate or molybdate, sulfosuccinate combined with nano-alumina provides more nucleation points, which can directionally control the growth path of the crystal, inhibit the by-product crystal phase, and improve the aspect ratio and mechanical strength of α-gypsum.

[0010] On the basis of the above technical scheme, preferably, the dosage of the additive is 5%-10% of the weight of the calcium sulfate dihydrate after impurities are removed. Calculated based on the weight percentage of 100%, the components of the additive include 0.05%-0.2% tungstate or molybdate, 0.2%-0.3% sulfosuccinate, 0.05%-0.3% nano alumina, and the balance is water.

[0011] On the basis of the above technical scheme, preferably, the impurity removal method of calcium sulfate dihydrate is: mixing calcium sulfate dihydrate with dilute acid, grinding it and filtering it, washing the precipitate with water 2-3 times and filtering and drying it to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0012] On the basis of the above technical solution, preferably, the dilute acid is dilute hydrochloric acid, and the concentration of the dilute hydrochloric acid is 7v%-10v%.

[0013] On the basis of the above technical solution, preferably, the additive further comprises amino acids, and the amount of the amino acids is 0.3% to 0.4% of the total weight of the additive.

[0014] On the basis of the above technical solution, preferably, the amino acid is one or more combinations of glycine, glutamic acid, lysine and aspartic acid.

[0015] Amino acids further adjust the catalyst system, strengthen the directional guidance during crystal growth, and inhibit the formation of impurities. 2 ) and carboxyl (-COOH) structures can chemically complex with the crystal surface, preferentially adsorb to specific crystal faces, and induce a more uniform whisker morphology. Different types of amino acids (such as glycine, glutamic acid, etc.) can inhibit or promote the growth of crystals in different directions, thereby enhancing the controllability of the aspect ratio and size distribution of whiskers.

[0016] Nano-alumina and amino acids interact with each other: on the one hand, they increase the nucleation points and improve the uniformity of crystal distribution; on the other hand, the selective adsorption of amino acids on the crystal growth surface ensures the consistency of the macroscopic morphology.

[0017] Glycine can provide an excellent crystal adsorption basis, regulate the anisotropic growth of crystals, and delay lateral growth to a certain extent, thereby promoting the formation of high aspect ratio whiskers; due to its simple molecule, it can also play a basic role in assisting in stabilizing the shape of whiskers.

[0018] Glutamic acid side chain contains additional carboxyl groups, which is a typical acidic amino acid. Its multi-carboxyl structure can preferentially bind to certain crystal surfaces through stronger adsorption force, selectively inhibit the growth of crystals in a specific direction, and enhance the ability to regulate the aspect ratio. Its side chain carboxyl groups also have a buffering effect on the pH of the reaction solution and the crystal growth rate, improving the morphological uniformity of the whiskers.

[0019] Aspartic acid is similar to glutamic acid, and its side chain contains a carboxyl group, which is an acidic amino acid. Aspartic acid rich in carboxyl groups enhances its coordination adsorption ability and has a high selective adsorption effect on the crystal surface; it can more effectively inhibit the radial growth of whiskers, enhance their aspect ratio, and improve the distribution consistency of whiskers.

[0020] Lysine has an amine group on its side chain and is a basic amino acid. The amine group can electrostatically adsorb to the sulfate group on the surface of the crystal, thereby stabilizing the surface structure of the whiskers and preventing lateral growth. Due to the alkalinity of lysine, it can neutralize the acidity in the local reaction environment, prevent the crystal morphology from getting out of control, and enhance the mechanical strength.

[0021] The four amino acids have the following synergistic effects: Glycine, as a simple molecule, provides universal crystal adsorption and morphology optimization. Glutamic acid and aspartic acid, as acidic amino acids, preferentially adsorb on specific crystal surfaces through the strong coordination of the carboxyl group, playing a directional induction role. Lysine improves the local crystal growth environment through the action of the amine group, inhibits disordered growth, increases the aspect ratio of the whiskers, and enhances the strength and morphological stability of the whiskers.

[0022] On the basis of the above technical solution, preferably, the additive further comprises microcrystalline cellulose, and the amount of the microcrystalline cellulose is 0.2% to 0.4% of the total weight of the additive.

[0023] Microcrystalline cellulose provides a skeleton support for the crystals, further improving the stability and regularity of the product. Principle: Microcrystalline cellulose forms a support network in the reaction medium, which reduces the collapse or adhesion of the whisker crystals during their growth, ultimately making the product more regular. At the same time, cellulose helps the whiskers form aggregates, improving the strength of the product.

[0024] On the basis of the above technical solution, preferably, the tungsten compound is sodium tungstate or ammonium metatungstate, and the molybdenum compound is sodium molybdate or ammonium metamolybdate.

[0025] On the other hand, the present invention also provides calcium sulfate hemihydrate, which is prepared by the above method.

[0026] The method for preparing calcium sulfate hemihydrate by using calcium sulfate dihydrate of the present invention has the following beneficial effects compared with the prior art: The tungstate or molybdate, sulfosuccinate and nano-alumina in the additive of the present invention are combined to adjust the crystal growth environment, provide more nucleation points, directionally control the growth path of the crystal, and inhibit the by-product crystal phase, so as to achieve the purpose of improving the aspect ratio and mechanical strength of α-type gypsum.

[0027] Amino acids further adjust the catalyst system through the amine and carboxyl groups on their molecules, strengthen the directional guidance during crystal growth, enhance the controllability of the aspect ratio and size distribution of whiskers, and inhibit the generation of impurities.

[0028] Microcrystalline cellulose provides a skeleton support for the crystals, reducing the collapse or adhesion of the whisker crystals during their growth, and further improving the stability, regularity and strength of the product. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1 The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, calcium sulfate dihydrate impurity removal: 3000g calcium sulfate dihydrate was mixed with 3500mL 8v% dilute hydrochloric acid, and the mixture was finely ground by ball mill (less than 100 mesh), and filtered. The precipitate was washed with water three times, and then filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0031] S2, take 2000g of calcium sulfate dihydrate after impurities are removed and add it into a high-pressure reactor, add 160g of additives and mix them evenly, then place it in a high-pressure container and react at 0.8MPa and 170°C for 25min; the additives are calculated based on 100% by weight, including 0.15% sodium tungstate, 0.26% sulfosuccinate, 0.25% nano-alumina, and the balance is water.

[0032] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 110° C. for 25 min, and dried to obtain calcium sulfate hemihydrate.

[0033] Example 2 The additives of this embodiment are based on the Example 1 and have added amino acids, which are as follows: The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, calcium sulfate dihydrate impurity removal: 3000g calcium sulfate dihydrate was mixed with 3500mL 8v% dilute hydrochloric acid, and the mixture was finely ground by ball mill (less than 100 mesh), and filtered. The precipitate was washed with water three times, and then filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0034] S2, take 2000g of calcium sulfate dihydrate after impurity removal and add it into a high-pressure reactor, add 160g of additives and mix them evenly, then place it in a high-pressure container and react at 0.8MPa and 170°C for 25min; the additives are calculated based on 100% by weight, including 0.15% sodium tungstate, 0.26% sulfosuccinate, 0.25% nano alumina, 0.15% glutamic acid + 0.15% aspartic acid + 0.1% lysine, and the balance is water.

[0035] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 110° C. for 25 min, and dried to obtain calcium sulfate hemihydrate.

[0036] Example 3 The additives of this embodiment are based on the embodiment 2 and have microcrystalline cellulose added, which are as follows: The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, calcium sulfate dihydrate impurity removal: 3000g calcium sulfate dihydrate was mixed with 3500mL 8v% dilute hydrochloric acid, and the mixture was finely ground by ball mill (less than 100 mesh), and filtered. The precipitate was washed with water three times, and then filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0037] S2, take 2000g of calcium sulfate dihydrate after impurity removal and add it into a high-pressure reactor, add 160g of additives and mix them evenly, then place it in a high-pressure container and react at 0.8MPa and 170°C for 25min; the additives are calculated based on 100% by weight, including 0.15% sodium tungstate, 0.26% sulfosuccinate, 0.25% nano alumina, 0.15% glutamic acid + 0.15% aspartic acid + 0.1% lysine, 0.28% microcrystalline cellulose, and the balance is water.

[0038] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 110° C. for 25 min, and dried to obtain calcium sulfate hemihydrate.

[0039] Example 4 The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, impurity removal of calcium sulfate dihydrate: 3000g of calcium sulfate dihydrate was mixed with 3500mL of 7v% dilute hydrochloric acid, and the mixture was finely ground by a ball mill (less than 100 meshes), and the precipitate was washed with water twice and filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0040] S2, take 2000g of calcium sulfate dihydrate after impurity removal and add it into a high-pressure reactor, add 120g of additives and mix them evenly, then place it in a high-pressure container and react at 0.13 MPa and 130°C for 30 minutes; the additives are calculated based on 100% by weight, including 0.05% sodium tungstate, 0.23% sulfosuccinate, 0.25% nano-alumina, 0.25% glutamic acid, 0.1% aspartic acid, 0.35% microcrystalline cellulose, and the balance is water.

[0041] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 100° C. for 30 min, and dried to obtain calcium sulfate hemihydrate.

[0042] Example 5 The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, impurity removal of calcium sulfate dihydrate: 3000g of calcium sulfate dihydrate was mixed with 3500mL of 9v% dilute hydrochloric acid, and the mixture was finely ground by a ball mill (less than 100 meshes), and the precipitate was washed with water three times and filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0043] S2, take 2000g of calcium sulfate dihydrate after impurity removal and add it to a high-pressure reactor, add 100g of additives and mix them evenly, then place it in a high-pressure container and react at 0.1 MPa and 120°C for 22 minutes; the additives are calculated based on 100% by weight, including 0.15% ammonium metatungstate, 0.28% sulfosuccinate, 0.15% nano alumina, 0.1% glutamic acid + 0.1% aspartic acid + 0.05% lysine + 0.05% glycine, 0.2% microcrystalline cellulose, and the balance is water.

[0044] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 120° C. for 10 min, and dried to obtain calcium sulfate hemihydrate.

[0045] Example 6 The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, impurity removal of calcium sulfate dihydrate: 3000g of calcium sulfate dihydrate was mixed with 3500mL of 10v% dilute hydrochloric acid, and the mixture was finely ground by a ball mill (less than 100 meshes), and the precipitate was washed with water twice and filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0046] S2, take 2000g of calcium sulfate dihydrate after impurity removal and add it into a high-pressure reactor, add 200g of additives and mix them evenly, then place it in a high-pressure container and react at 0.18 MPa and 140°C for 24 minutes; the additives are calculated according to 100% by weight, including 0.2% ammonium metamolybdate, 0.2% sulfosuccinate, 0.3% nano-alumina, 0.35% lysine, 0.28% microcrystalline cellulose, and the balance is water.

[0047] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 115° C. for 14 min, and dried to obtain calcium sulfate hemihydrate.

[0048] Example 7 The method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate in this embodiment comprises the following steps: S1, calcium sulfate dihydrate impurity removal: 3000g calcium sulfate dihydrate was mixed with 3500mL 8v% dilute hydrochloric acid, and the mixture was finely ground by ball mill (less than 100 mesh), and filtered. The precipitate was washed with water three times, and then filtered to obtain the residue, which was dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

[0049] S2, take 2000g of calcium sulfate dihydrate after impurity removal and add it into a high-pressure reactor, add 180g of additives and mix them evenly, then place it in a high-pressure container and react at 2 MPa and 160°C for 20 minutes; the additives are calculated based on 100% by weight, including 0.15% sodium tungstate, 0.3% sulfosuccinate, 0.05% nano-alumina, 0.18% glutamic acid + 0.17% lysine, 0.4% microcrystalline cellulose, and the balance is water.

[0050] S3, after the reaction is completed, the reactants are placed in a forced air dryer, treated at 118° C. for 11 min, and dried to obtain calcium sulfate hemihydrate.

[0051] Comparative Example 1 Compared with Example 1, Comparative Example 1 lacks sodium tungstate as an additive, and the rest of the contents are the same as Example 1.

[0052] Comparative Example 2 Compared with Example 1, Comparative Example 2 lacks nano-alumina as an additive, and the rest of the contents are the same as Example 1.

[0053] Comparative Example 3 Compared with Example 1, the additive of Comparative Example 3 lacks sulfosuccinate, and the rest of the contents are the same as Example 1.

[0054] Comparative Example 4 Compared with Example 1, the amount of additive in Comparative Example 4 exceeds the limited range (5%-10%), and the specific amount is 15%. The rest of the contents are the same as Example 1.

[0055] Comparative Example 5 Compared with Example 2, the amount of amino acids in Comparative Example 5 exceeds the limited range (0.3%~0.4%), and the specific amount is 0.5%, glutamic acid 0.35%, and aspartic acid 0.15%. The rest of the content is the same as Example 2.

[0056] Comparative Example 6 In Comparative Example 6, compared with Example 3, the amount of microcrystalline cellulose exceeds the limited range (0.2%-0.4%), and the specific amount is 0.5%. The rest of the contents are the same as Example 3.

[0057] The calcium sulfate hemihydrate prepared in the embodiment and the comparative example is α calcium sulfate hemihydrate, and its strength is tested with reference to the industry standard JC / T 2038-2010, and the results are as follows:

[0058] As shown in Table 1, it can be seen from Examples 1-3 that the aspect ratio and strength of calcium sulfate hemihydrate are significantly improved after adding amino acids (see Example 2). This is because glutamic acid and aspartic acid are adsorbed on the crystal surface through the strong coordination of the carboxyl group, which plays a directional induction role, thereby improving the aspect ratio of the whiskers. Lysine improves the local crystal growth environment through the action of the amine group, inhibits disordered growth, improves the aspect ratio of the whiskers, and enhances the strength and morphological stability of the whiskers. The strength is greatly improved after adding microcrystalline cellulose (see Example 3). This is because microcrystalline cellulose provides skeleton support for the crystals, which reduces the collapse or adhesion of the whisker crystals during the growth process, thereby improving the strength of the product.

[0059] It can be seen from Comparative Examples 1-3 that the lack of any one of sodium tungstate, nano-alumina and sulfosuccinate will affect the aspect ratio and strength of calcium sulfate hemihydrate. This is because tungstate or molybdate, sulfosuccinate and nano-alumina have a synergistic effect. Nano-alumina provides more nucleation points, allowing the crystals to be evenly distributed; sulfosuccinate inhibits particle aggregation, and the ions of tungstate and molybdate are adsorbed on the crystal interface or growth front, inducing its one-dimensional growth, while reducing the crystal extension behavior in other directions, thereby achieving the formation of slender whiskers.

[0060] Comparative Examples 4-6 show that the amount of additives, amino acids, and microcrystalline cellulose is not the more the better. Excessive use of tungstate / molybdate or nano-alumina will lead to too many nucleation points in the system, and the crystals cannot fully carry out directional growth, and the whiskers cannot form a mesh skeleton that is interwoven with each other, and the aspect ratio is reduced, and the system density and mechanical properties are reduced. When the amount of amino acids exceeds the standard, an overly thick adsorption layer will be formed, which hinders the extension of the crystal in a specific direction. In addition, excessive amino acids will cause the whiskers to be unable to be interwoven into a network skeleton due to poor directionality, and the dry compressive strength will not increase but decrease. When the amount of microcrystalline cellulose is too much, the viscosity of the system will be significantly increased, the diffusion performance in the solution will deteriorate, the nucleation rate of calcium sulfate in the system will be reduced, the full extension of the crystal will be inhibited, and the aspect ratio will be reduced; when the amount of microcrystalline cellulose is too large, its strong water absorption will expand to form a large amount of gel, and more cellulose pores will remain in the product, resulting in a decrease in the overall density of the system and a significant reduction in strength. Therefore, it is the key to achieve the best aspect ratio and compressive strength performance to reasonably control the amount within the design range.

[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate, characterized in that: The following steps are involved: S1, calcium sulfate dihydrate impurity removal; S2, the calcium sulfate dihydrate after impurity removal is evenly mixed with the additive, and then placed in a high-pressure container, and reacted at 0.1-2MPa and 120-170°C for 20-30min; The additive comprises transition metal oxyacid salt, sulfosuccinate, nano-alumina and water, wherein the transition metal oxyacid salt is tungstate or molybdate; S3, after the reaction is completed, the reactant is dried at 100° C.-120° C. to obtain calcium sulfate hemihydrate.

2. A method for preparing calcium sulfate hemihydrate by utilizing calcium sulfate dihydrate as claimed in claim 1, characterized in that: The dosage of the additive is 5%-10% of the weight of the calcium sulfate dihydrate after impurities are removed.

3. A method for preparing calcium sulfate hemihydrate by utilizing calcium sulfate dihydrate as claimed in claim 1, characterized in that: Calculated based on 100% by weight, the additive comprises 0.05% to 0.2% tungstate or molybdate, 0.2% to 0.3% sulfosuccinate, 0.05% to 0.3% nano-alumina, and the balance is water.

4. A method for preparing calcium sulfate hemihydrate by utilizing calcium sulfate dihydrate as claimed in claim 1, characterized in that: The impurity removal method of calcium sulfate dihydrate is as follows: calcium sulfate dihydrate is mixed with dilute acid, ground, filtered, the precipitate is washed with water 2-3 times, filtered, and dried to obtain the impurity-removed calcium sulfate dihydrate intermediate product.

5. A method for preparing calcium sulfate hemihydrate by utilizing calcium sulfate dihydrate as claimed in claim 4, characterized in that: The dilute acid is dilute hydrochloric acid, and the concentration of the dilute hydrochloric acid is 7v%-10v%.

6. A method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate as claimed in claim 1, characterized in that: The additive also includes amino acids, and the amount of the amino acids used is 0.3% to 0.4% of the total weight of the additive.

7. A method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate as claimed in claim 6, characterized in that: The amino acids are one or more combinations of glycine, glutamic acid, lysine and aspartic acid.

8. A method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate as claimed in claim 6, characterized in that: The additive also includes microcrystalline cellulose, and the amount of the microcrystalline cellulose is 0.2% to 0.4% of the total weight of the additive.

9. A method for preparing calcium sulfate hemihydrate using calcium sulfate dihydrate as claimed in claim 1, characterized in that: The tungstate is sodium tungstate or ammonium metatungstate, and the molybdate is sodium molybdate or ammonium metamolybdate.

Citation Information

Patent Citations

  • Method for preparing Alpha type calcium sulfate hemihydrate from calcium sulphate dihydrate

    CN105948547A

  • Method for preparing calcium sulfate hemihydrate whiskers with high length-diameter ratio by using calcium sulfate dihydrate

    CN110541188A

  • Calcium sulfate reinforced in-situ curing pore-forming tissue engineering polyester composite scaffold material as well as preparation method and application thereof

    CN114438597A

  • Ternary positive electrode material with crystal face growth regulated and controlled by molybdate and preparation method of ternary positive electrode material

    CN116969519A

  • Method for producing alpha gypsum by using citric acid gypsum

    CN118373616A